Telomere dynamic in humans and animals: Review and perspectives in environmental toxicology. (October 2019) - Louzon, Maxime; Coeurdassier, Michael; Gimbert, Frédéric; Pauget, Benjamin; de Vaufleury, Annette
Abstract: Telomeres (TLs) play major roles in stabilizing the genome and are usually shortened with ageing. The maintenance of TLs is ensured by two mechanisms involving telomerase (TA) enzyme and alternative lengthening telomeres (ALT). TL shortening and/or TA inhibition have been related to health effects on organisms (leading to reduced reproductive lifespan and survival), suggesting that they could be key processes in toxicity mechanisms (at molecular and cellular levels) and relevant as an early warning of exposure and effect of chemicals on human health and animal population dynamics. Consequently, a critical analysis of knowledge about relationships between TL dynamic and environmental pollution is essential to highlight the relevance of TL measurement in environmental toxicology. The first objective of this review is to provide a survey on the basic knowledge about TL structure, roles, maintenance mechanisms and causes of shortening in both vertebrates (including humans) and invertebrates. Overall, TL length decreases with ageing but some unexpected exceptions are reported ( e.g., in species with different lifespans, such as the nematode Caenorhabditis elegans or the crustacean Homarus americanus ). Inconsistent results reported in various biological groups or even between species of the same genus ( e.g., the microcrustacean Daphnia sp. ) indicate that the relation usually proposed between TL shortening and a decrease in TA activity cannot be generalized and depends on the species, stage of development or lifespan. Although the scientific literature provides evidence of the effect of ageing on TL shortening, much less information on the relationships between shortening, maintenance of TLs, influence of other endogenous and environmental drivers, including exposure to chemical pollutants, is available, especially in invertebrates. The second objective of this review is to connect knowledge on TL dynamic and exposure to contaminants. Most of the studies published on humans rely on correlative epidemiological approaches and few in vitro experiments. They have shown TL attrition when exposed to contaminants, such as polycyclic aromatic hydrocarbons (PAH), polychlorinated biphenyls (PCB), pesticides and metallic elements (ME). In other vertebrates, the studies we found deals mainly with birds and, overall, report a disturbance of TL dynamic consecutively to exposure to chemicals, including metals and organic compounds. In invertebrates, no data are available and the potential of TL dynamic in environmental risk assessment remains to be explored. On the basis of the main gaps identified some research perspectives ( e.g., impact of endogenous and environmental drivers, dose response effects, link between TL length, TA activity, longevity and ageing) are proposed to better understand the potential of TL and TA measurements in humans and animals in environmental toxicology. Highlights: Telomere attrition with ageing is not a generality in Animal Kingdom. Exposure to pollutants can cause shortening or lengthening of telomeres depending on the chemical considered. In invertebrates, the potential of telomere dynamic in environmental risk assessment remains to be explored.